Investigating stakeholder engagement and absorptive capacity as drivers of green innovations at German 3PL companies - Bálint, M.; Silva, J.; Möhring, M. (Proceedings of the 28th International Annual EurOMA Conference 2021, 2021)
Research on environmental sustainability from the third-party logistics provider’s (3PL) perspective is claimed to be descriptive, focusing mainly on ecological practices’ initial development. Thus, this paper emphasises 3PL companies’ adaptation to changing environments and recognises stakeholder engagement and absorptive capacity as capabilities needed to maintain sustainability practices over time. Findings indicate that stakeholder engagement mechanisms ensure adapting to stakeholders’ knowledge and requirements in environmental matters, whereas capabilities that allow the integration and transformation of sustainability-related knowledge are expected to help 3PLs successfully implement and commercialise green innovation.